Pendidikan Moral Remaja Dalam Keluarga Single Parent Di Desa Monggot Kecamatan Geyer Kabupaten Grobogan Tahun 2015 - Choyruddin, Ahmad, Dr. Abdullah 'Aly, M.Ag, Drs. Abdullah Mahmud, M.Ag (2015)
Education in all civilizations uma tmanusia from ancient times until today. Moreover, moral education in life today is very necessary because man is created olehTuhan have moral instincts. Morals that make certain norms act as a tool in life. The rise of the phenomenon of single parent or single parent in today's society become commonplace or ordinary. Single parent requires the dual role of a single parent to always pay attention to moral child, so the child does not lose grip in his life to be. The morality of parents in the family to be one example of moral education that taught parents to children because the child will naturally absorb what do parents. Based on this background, the purpose of this study is to determine the methods used single parent in educating young people in the village Monggot moral District of Geyer Grobogan and inhibiting factors. This research is a field (field research) by using a type of qualitative approach, the study aimed to describe and analyze the phenomena, events, aktivitassosial, attitudes, beliefs, perceptions, thoughts people individually or in groups. The method used to collect data that is the method of interview, documentation and observation. While the techniques of data analysis was done by descriptive qualitative. Based on the analysis of research data, it can be concluded that the method used by single parent families in the village Monggot in adolescent moral education is exemplary method, a good method of habituation, the method of advice, supervision and methods of observation method of punishment. The inhibiting factor of moral education in single parent families in the village Monggot divided into two factors: internal factors and external factors. Internal factors are factors that comes from within the person the child as the child who often ignore the words of parents and children who tend to be quiet nature. While external factors are factors originating from outside of the child such as busyness and time constraints of parents single parent, low knowledge of religion parent single parent, and economic limitations.